1985
DOI: 10.1007/bf01644233
|View full text |Cite
|
Sign up to set email alerts
|

Impact of injectable cephalosporins on the gastrointestinal microflora: Observations in healthy volunteers and hospitalized patients

Abstract: A disturbed microbiological ecosystem of the gut flora is frequently seen as a consequence of antibiotic therapy. Because this impact on the physiological balance is known to be causative for severe nosocomial infections and is mainly seen with antibiotics that are massively excreted via the bile (e.g. broadspectrum penicillins, ceftriaxone and cefoperazone), we investigated cefotaxime (CTX), cefotiam (CTM), cefmenoxime (CMX), ceftazidime (CAZ), ceftizoxime (CZX) and cefazolin + netilmicin (CEZ + NTL) in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Resistance to ceftazidime was not observed 62 . Similar findings were observed in a study performed by Knothe and colleagues 63 …”
Section: Effect Of Antimicrobial Therapy On the Gut Microbiomesupporting
confidence: 86%
See 1 more Smart Citation
“…Resistance to ceftazidime was not observed 62 . Similar findings were observed in a study performed by Knothe and colleagues 63 …”
Section: Effect Of Antimicrobial Therapy On the Gut Microbiomesupporting
confidence: 86%
“…The impact of ceftazidime on the faecal microbiome was studied in eight healthy volunteers. As expected, the intestinal Enterobacteriaceae content was suppressed at the end of the treatment course 62 , 63 . Intestinal anaerobic organisms such as Lactobacillus bifidus had a slight decrease and Bacteroides fragilis had minimal fluctuations overall.…”
Section: Effect Of Antimicrobial Therapy On the Gut Microbiomesupporting
confidence: 74%
“…Antibiotic therapy can disturb the indigenous intestinal flora, resulting in a significant decrease in Lactobacillus spp. (3,20,21), which is a common problem in treatment of infectious diseases and postoperative septic complications (17). A patient with a suppressed indigenous flora is more susceptible to secondary infections and overgrowth of undesired microorganisms, leading to diarrhea and even pseudomembraneous colitis and development of distant organ failure (5,17,22).…”
mentioning
confidence: 99%
“…Jones (1985) also reported that the incidence of enterococcal superinfection after Ctx therapy was lower than that in patients given other betalactam antibiotics. Cefotaxime is also thought to affect the human faecal flora less than other third generation cephalosporins (Knothe, Dette & Shah, 1985;Burdon et al 1985). However, reported results in this area are difficult to evaluate: Lambert-Zechovsky et al (1985) described a rise in the faecal enterococci in children treated with Ctx whereas Guggenbichler and co-workers (1985) demnonstrated a similar rise in only 1 of 20 treated children.…”
Section: Discussionmentioning
confidence: 99%